2016
DOI: 10.4103/0972-5229.194012
|View full text |Cite
|
Sign up to set email alerts
|

Refractory pediatric cardiogenic shock: A case for mechanical support

Abstract: Acute left ventricular dysfunction in children justifies aggressive treatment because of the high potential for complete recovery. The options for providing mechanical support to the failing heart in a child include extracorporeal membrane oxygenation, left ventricular assist devices, and the use of the intra-aortic balloon pump (IABP). The IABP is a commonly used method of temporary circulatory support in adults. However, despite the availability of pediatric size balloons, the usage of IABP for temporary cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…We observed that persistently high gO 2 ER and lack of attainment of critical DO 2 in the initial phases of therapy may identify children in septic shock with chronic tissue oxygen debt progressing to an irreversible shock state and death. This suggests that early options of treatment above the standard is needed in the above sub-set of children, for example, inodilators such as milrinone or levosimendan, or even extracorporeal membrane oxygenation (ECMO) to attain critical DO 2 and save life ( 33 ) ( 34 ). This is because our data suggest that the DO 2 was far short of matching the oxygen need or consumption especially amongst non-survivors.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that persistently high gO 2 ER and lack of attainment of critical DO 2 in the initial phases of therapy may identify children in septic shock with chronic tissue oxygen debt progressing to an irreversible shock state and death. This suggests that early options of treatment above the standard is needed in the above sub-set of children, for example, inodilators such as milrinone or levosimendan, or even extracorporeal membrane oxygenation (ECMO) to attain critical DO 2 and save life ( 33 ) ( 34 ). This is because our data suggest that the DO 2 was far short of matching the oxygen need or consumption especially amongst non-survivors.…”
Section: Discussionmentioning
confidence: 99%